Veronica plants-drifting from farm to traditional healing, food application, and phytopharmacology - Salehi, B (2019)
The Veronica genus, with more than 200 species, belongs to the Plantaginaceae family and is distributed over most of the Northern Hemisphere and in many parts of Southern Hemisphere. These plants are traditionally used in medicine for wound healing, in the treatment of rheumatism, and in different human diseases. This paper reviews the chemical composition of some valuable Veronica species, the possibilities Veronica extracts have in food preservation and as food ingredients, and their functional properties. Veronica species represent a valuable source of biological active secondary metabolites, including iridoid glycosides and phenolic compounds. In particular, due to presence of these phytochemicals, Veronica species exhibit a wide spectrum of biological activities, including antimicrobial and antioxidant. In fact, some studies suggest that some Veronica extracts can inhibit foodborne pathogens, such as Listeria monocytogenes, but only a few of them were performed in food systems. Moreover, anticancer, anti-inflammatory, and other bioactivities were reported in vitro and in vivo. The bioactivity of Veronica plants was demonstrated, but further studies in food systems and in humans are required.